Molecular phylogeny of Sericostomatoidea (Trichoptera) with the establishment of three new families. (30th September 2016) - JOHANSON, KJELL ARNE; MALM, TOBIAS; ESPELAND, MARIANNE
Abstract: We inferred the phylogenetic relationships among 58 genera of Sericostomatoidea, representing all previously accepted families as well as genera that were not placed in established families. The analyses were based on five fragments of the protein coding genes carbamoylphosphate synthetase (CPSase of CAD), isocitrate dehydrogenase (IDH), Elongation factor 1a (EF‐1a), RNA polymerase II (POL II) and cytochrome oxidase I (COI). The data set was analysed using Bayesian methods with a mixed model, raxml, and parsimony. The various methods generated slightly different results regarding relationships among families, but the shared results comprise support for: (i) a monophyletic Sericostomatoidea; (ii) a paraphyletic Parasericostoma due to inclusion of Myotrichia murina, leading to synonymization of Myotrichia with Parasericostoma ; (iii) a polyphyletic Sericostomatidae, which is divided into two families, Sericostomatidae sensu stricto and Parasericostomatidaefam.n. ; (iv) a polyphyletic Helicophidae which is divided into Helicophidae sensu stricto and Heloccabucidaefam.n. ; (v) hypothesized phylogenetic placement of the former incerta sedis genera Ngoya, Seselpsyche and Karomana ; (vi) a paraphyletic Costora (Conoesucidae) that should be divided into several genera after more careful examination of morphological data; (vii) reinstatement of Gyrocarisa as a valid genus within Petrothrincidae. A third family, Ceylanopsychidaefam.n., is established based on morphological characters alone. A hypothesis of the relationship among 14 of the 15 families in the superfamily is presented. A key to the families is presented based on adults (males). Taxonomic history, diagnosis, habitat preference and distribution data for all sericostomatoid families are presented. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:CF6A6B9F‐6A72‐4265‐BD09‐3A710DFCD7B1 .